Author Correction: Observation of half-integer thermal Hall conductance. (11th October 2018) - Banerjee, Mitali; Heiblum, Moty; Umansky, Vladimir; Feldman, Dima; Oreg, Yuval; Stern, Ady
In this Article, the publication details for references 33, 34 and 40 have been corrected online.